2023
DOI: 10.1002/apj.2900
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization of a novel bionic fractal microchannel applied in thermal management of electronic components

Abstract: Reducing energy consumption and improving device efficiency are important ways to realize efficient heat dissipation of microdevices, this paper developed a new bionic fractal microchannel heat sink based on fractal theory and topological optimization ideas, which introduced a binary flow stagnation zone optimization based on topological optimization ideas on the basic fractal microchannel. The thermal and hydraulic properties of a nanofluid in a fractal microchannel heat sink (FMCHS) have been numerically sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Figure 7a depicts the simulated and theoretically calculated values of the f ave at different Res. The theoretical value of the f ave can be calculated using Equation (13). The simulation results and the theoretical results are in agreement, with a largest relative error of approximately 1%.…”
Section: Model Validationsupporting
confidence: 56%
See 1 more Smart Citation
“…Figure 7a depicts the simulated and theoretically calculated values of the f ave at different Res. The theoretical value of the f ave can be calculated using Equation (13). The simulation results and the theoretical results are in agreement, with a largest relative error of approximately 1%.…”
Section: Model Validationsupporting
confidence: 56%
“…The simulation and experimental results showed that the microchannel aspect ratio had a great impact on its characteristics. Wang et al [13] developed a new bionic fractal microchannel heat sink based on the fractal theory and topological optimization ideas. The results showed that the introduction of the optimization increased the central velocity of the microchannel by 7.14-18.2%.…”
Section: Introductionmentioning
confidence: 99%